Interactive television? A retrospective analysis of why red button content failed. (1st June 2019) - Fox, Andy
Interactive television was intended to provide the viewers with an enhanced experience of television. In the late 1990s and early 2000s, both public service and subscription-based television broadcasters provided the audience with a variety of 'interactive' applications. By 2012, most of the interactive applications had been either reduced in scale and ambition or withdrawn completely. This article is an overview of why the interactive television experiment failed. The methodological framework is a content analysis undertaken in the summer of 2012 which found a small amount of red button content supporting traditional broadcasts. The little found was either pre-existing content or entailed the button's use as, effectively, the portal to a supplementary television channel. Moving forward, the article provides a discussion on why the optimism that television could be an interactive experience in the early 2000s dissolved in a relatively short period of time. The conclusion is that interactive television did not fit the political economy of the media landscape.